Saberes Etnoictiológicos dos Pescadores Artesanais nos Açudes do Alto Rio Acaraú, Ceará, Brasil - Batista, Leidiane Priscilla de Paiva (2012)
The ethnoictiology to describe and use the knowledge of fishermen, by studies that show that they are carriers of bio-ecological knowledge about fish they catch. Thus, the objective was to compare the knowledge of fishermen of public dams Araras and Edson Queiroz (Middle Acaraú River Basin, Ceará) with the scientific literature. With this end, we selected a representative population for each of these reservoirs. Therefore, there is the Ilha de Esaú, for the dam Araras, and Vila São Cosme, to Edson Queiroz. Were performed participant observation, semi-structured interviews, visual stimulus, and guided fishing tours of these populations. Twenty fishermen were interviewed in Vila Sao Cosme and twenty-four on the Ihla de Esaú The interviews aspects ethnoecological of the main fish species caught by fishermen. Were cited twenty ethnospecies fish and shrimp as captured in the reservoirs. Among these, the most important, economically, are cará-tilapia [Oreochromis niloticus (Linnaeus, 1758) and Tilapia rendalli (Boulenger, 1897)], curimatã [(Prochilodus brevis (Steindachner, 1874)], pescada [Plagiossion squamossimus (Heckel, 1840)], piau (Leporinus sp.),traíra (Hoplias brasiliensis e H. malabaricus) and tucunaré [Cichla cf. ocellaris (Bloch; Schneider, 1801)]. In the classification of fishes, fishemen used morphological and ethological aspects, presenting several ethnospecies with generic names and few with binomial names. In your diet, these populations consume fish as the main source of animal protein, with social and cultural restrictions. As for ethnoictiology, it is concluded that the fishermen have consistent knowledge about the general ecology, trophic and reproductive of fishes captured. Therefore, the consistency of the knowledge of fishermen on the Ilha de Esaú and Vila São Cosme, this knowledge can contribute to future scientific studies and be incorporated in the preparation of management plans and sustainable management of water resources and fisheries in the middle region Acaraú.